1989
DOI: 10.1007/bf00221649
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of islet amyloid peptide in lipofuscin bodies and secretory granules of human B-cells and in islets of type-2 diabetic subjects

Abstract: Islet amyloid peptide (or diabetes-associated peptide), the major component of pancreatic islet amyloid found in type-2 diabetes, has been identified by electron-microscopic immunocytochemistry in pancreatic B-cells from five non-diabetic human subjects, and in islets from five type-2 diabetic patients. The greatest density of immunoreactivity for islet amyloid peptide was found in electron-dense regions of some lysosomal or lipofuscin bodies. The peptide was also localised by quantification of immunogold in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(54 citation statements)
references
References 27 publications
3
51
0
Order By: Relevance
“…In ␤-cells and other secretory cells, proteins that are not sorted to granules (e.g., receptors) can be delivered to the plasma membrane and/or secreted via the constitutive pathway. Although the ␤-cell peptide IAPP is colocalized with insulin in secretory granules (4,5) and can be released from ␤-cells by the regulated secretory pathway, our findings demonstrate that a significant proportion (~40%) of glucose-stimulated IAPP release occurs via the constitutive secretory pathway in neonatal rat ␤-cells.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In ␤-cells and other secretory cells, proteins that are not sorted to granules (e.g., receptors) can be delivered to the plasma membrane and/or secreted via the constitutive pathway. Although the ␤-cell peptide IAPP is colocalized with insulin in secretory granules (4,5) and can be released from ␤-cells by the regulated secretory pathway, our findings demonstrate that a significant proportion (~40%) of glucose-stimulated IAPP release occurs via the constitutive secretory pathway in neonatal rat ␤-cells.…”
Section: Discussionmentioning
confidence: 62%
“…IAPP is synthesized primarily in the pancreatic ␤-cell, where it is colocalized with insulin in secretory granules (4,5) and is released along with insulin in response to stimulation by ␤-cell secretagogues such as glucose (6,7). The physiological function of IAPP has not been determined, although effects on insulin action (8) and secretion (9), gastric emptying (10), and food intake (11) have all been suggested.…”
mentioning
confidence: 99%
“…It has been suggested that IAPP most probably occurs in the translucent halo [19,20] although in one immune electron microscopy study the strongest IAPP immunoreactivity was found on the granule cores [5]. This latter finding could possibly be due to a preparation artefact but it could not be ruled out that lAPP is stored together with insulin on the granule core surface.…”
Section: Discussionmentioning
confidence: 94%
“…Under normal conditions, beta-cell granules including intracellular IAPP and insulin which are not targeted for secretion, are degraded in lysosomes [107] and human IAPP accumulates in lysosomes in islets from man and hIAPP transgenic mice [108,109]; however, there was no evidence of IAPP fibril formation in lysosomes indicating that an increased concentration is not sufficient for intracellular fibril formation at this site. A proposal has been made that all amyloid deposits are being degraded continuously [110], possibly by removal by macrophages, and that accumulation of deposits could result from a deficiency in the factors responsible for degradation and/or turnover [111].…”
Section: Iapp Concentrationmentioning
confidence: 99%